PROSES BERPIKIR KREATIF SISWA DENGAN KEMAMPUAN MATEMATIKA TINGGI DALAM MENYELESAIKAN SPLDV - Titis wulan yuliani; Masriyah; Agung Lukito (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study describes the creative thinking process of a junior high school student with high mathematical ability in solving a system of linear equations in two variables (SPLDV). A descriptive qualitative approach was applied. The research subject was one student categorized as having high mathematical ability, selected based on a Mathematical Ability Test and good communication skills during the interview. Data were collected through Problem Solving Task (PST) and a semi-structured interview, then analyzed using the problem-solving stages of Krulik and Rudnick (1995) combined with Silver's (1997) creativity indicators, namely fluency, flexibility, and novelty. The results show that the subject understood the problem thoroughly, formulated an accurate mathematical model, and solved the problem using two different methods, substitution and elimination. The subject also verified the answer by comparing the results of both methods. The novelty indicator did not appear, since the subject failed to construct a solution method different from the common method taught in class. These findings indicate that high mathematical ability strongly supports fluency and flexibility, while novelty still requires additional learning experience to emerge optimally.